Molecular mechanism of substrate selectivity of the arginine-agmatine Antiporter AdiC. Issue 1 (December 2018) - Krammer, Eva-Maria; Gibbons, Andrew; Roos, Goedele; Prévost, Martine
Abstract The arginine-agmatine antiporter (AdiC) is a component of an acid resistance system developed by enteric bacteria to resist gastric acidity. In order to avoid neutral proton antiport, the monovalent form of arginine, about as abundant as its divalent form under acidic conditions, should be selectively bound by AdiC for transport into the cytosol. In this study, we shed light on the mechanism through which AdiC distinguishes Arg+ from Arg2+ of arginine by investigating the binding of both forms in addition to that of divalent agmatine, using a combination of molecular dynamics simulations with molecular and quantum mechanics calculations. We show that AdiC indeed preferentially binds Arg+ . The weaker binding of divalent compounds results mostly from their greater tendency to remain hydrated than Arg+ . Our data suggests that the binding of Arg+ promotes the deprotonation of Glu208, a gating residue, which in turn reinforces its interactions with AdiC, leading to longer residence times of Arg+ in the binding site. Although the total electric charge of the ligand appears to be the determinant factor in the discrimination process, two local interactions formed with Trp293, another gating residue of the binding site, also contribute to the selection mechanism: a cation-π interaction with the guanidinium group of Arg+ and an anion-π interaction involving Glu208.